The Effect of High Intensity Interval Training on Muscular Biomarkers of Mitochondrial Biogenesis in Male Rats - F Sharafi Dehrhm; R Soori; M Rastegar MM; A Sadegh (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul, 2017)
BACKGROUND AND OBJECTIVE: PGC1α increases expression and coactivation of transcription factors for increases in mitochondria biogenesis-related genes. The purpose of the current study was to determine the effect of high intensity interval training on muscular biomarkers of mitochondrial biogenesis in male rats. METHODS: Type of research design in the current study was semi-experimental. In the current study 18 Wistar rats were separated into HIIT and control groups. HIIT protocol was done 60 min in each session for four sessions in each week. HIIT group was carried out 15×4 min bouts of HIIT with 85 to 90% of VO2max that sustained with three min recovery (between each bout of HIIT) with 70% of VO2max. PGC1α and Tfam and their gene translations were evaluated by commercial kits and Real-Time PCR method, respectively. FINDINGS: Outcomes indicated that serum levels of PGC1α (CI=8.5±1.02, 6.3 to 10.6) and Tfam (CI= 7.9±1.16, 5.42 to 10.33) were significantly increased. Also, PGC1α and Tfam gene expression in both fast- (1.14±0.13) and slow (1.1±0.16 muscles were significantly increased (p=0.003 and p=0.0001, respectively). CONCLUSION: It appears that, present HIIT protocol has capability to significant increase in both muscular and serum levels of biomarkers of mitochondrial biogenesis (PGC1α and Tfam) in male rats. Likewise, there is a possibility that HIIT essence is an inducer factor for further expression of this biomarkers in slow-twitch than fast-twitch muscles